2017
DOI: 10.5935/0101-2800.20170051
|View full text |Cite
|
Sign up to set email alerts
|

Benefcial effects of intradialytic cardiopulmonary rehabilitation

Abstract: The intradialytic CRehab applied in this population was safe and allowed objective improvement of functional capacity and exercise tolerance, subjective improvement in the perception of effort, significant increase in cardiac function and better quality of life in different domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Furthermore, after 2 months of training interruption, there was a significant decrease of 6MWT distance when compared to the exercise period, but this distance remained higher than the baseline period. 14 In other study, Kouidi et al 15 evaluated the effects of two types (intra-dialytic and extra-dialytic) of long-term exercise training in HD patients and observed that 4 years of exercise promoted continued improvement in peak oxygen uptake in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after 2 months of training interruption, there was a significant decrease of 6MWT distance when compared to the exercise period, but this distance remained higher than the baseline period. 14 In other study, Kouidi et al 15 evaluated the effects of two types (intra-dialytic and extra-dialytic) of long-term exercise training in HD patients and observed that 4 years of exercise promoted continued improvement in peak oxygen uptake in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Abaixo estão apresentados os valores referentes às médias gerais e desvio-padrão das variáveis PAS e PAD em repouso, após 20 sessões e após 40 sessões, de acordo com os horários de treinamento dos pacientes. Este tipo de estudo não é comum, pois nesta população a prescrição rotineira de exercícios físicos não é uma prática freqüente da mesma maneira que é realizado em pessoas consideradas normais, é necessário fazer uma avaliação individual para prescrever o volume e a intensidade do exercício para que não prejudique o seu tratamento [15].…”
Section: Resultados E Discussõesunclassified
“…Em 1986, Painter et al [15] desenvolveram o primeiro protocolo de exercício aeróbico durante as sessões de HD e chegaram aos resultados que seis meses de treinamento físico foi eficiente para aumentar o consumo de oxigênio além de reduzir uso de medicação antihipertensiva em alguns pacientes.…”
Section: Introductionunclassified
“…In total, six studies (total n5315) examined outcomes related to myocardial structure (Table 4). 32,53,55,60,64,66 4B). 53,60,64,66 Cardiac Autonomic Dysfunction/Increased Sympathetic Activity Four RCTs (total n5205) assessed the effect of intradialytic cycling for 30-90 minutes, thrice weekly over 12-52 weeks of duration on various measures of HRV (Table 4).…”
Section: Myocardial Structurementioning
confidence: 99%